2022
DOI: 10.1186/s12957-022-02800-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with non-small cell lung cancer treated with PD-1/PD-L1 inhibitors: a systematic review and meta-analysis

Abstract: Background Immune checkpoint inhibitors (ICIs) have dramatically prolonged survival in non-small cell lung cancer (NSCLC) patients, but little research had focused on its impact on quality of life (QoL). The purpose of our study was to compare the QoL in patients with NSCLC treated with programmed cell death protein-1/programmed cell death-ligand 1 (PD-1/PD-L1) inhibitors versus chemotherapy. Methods We searched for randomized controlled trials uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…For example, ICIs primarily target speci c immune checkpoints, resulting in fewer direct cytotoxic effects on healthy cells and organs and potentially leading to reduced pain levels [33]. Aligning with our ndings, a meta-analysis of ve RCTs found that PD-1/PD-L1 inhibitors led to longer times to rst clinically signi cant deterioration in HRQoL scores, as well as improvements in physical function and pain in patients with lung cancer [34]. A recent subgroup analysis of the CheckMate 649 trial showed more signi cant improvements in the FACT-Ga total, GaCS, and EQ-5D visual analog scale in patients receiving a combination of ICIs and chemotherapy than in patients receiving chemotherapy, with a reduction in HRQoL deterioration [35].…”
Section: Discussionsupporting
confidence: 76%
“…For example, ICIs primarily target speci c immune checkpoints, resulting in fewer direct cytotoxic effects on healthy cells and organs and potentially leading to reduced pain levels [33]. Aligning with our ndings, a meta-analysis of ve RCTs found that PD-1/PD-L1 inhibitors led to longer times to rst clinically signi cant deterioration in HRQoL scores, as well as improvements in physical function and pain in patients with lung cancer [34]. A recent subgroup analysis of the CheckMate 649 trial showed more signi cant improvements in the FACT-Ga total, GaCS, and EQ-5D visual analog scale in patients receiving a combination of ICIs and chemotherapy than in patients receiving chemotherapy, with a reduction in HRQoL deterioration [35].…”
Section: Discussionsupporting
confidence: 76%
“…Cancer immunotherapy strategies include ICIs, adoptive cell therapy, monoclonal antibodies, oncolytic virus immunotherapy, and vaccination [49]. ICIs are progressing rapidly, and have recently brought new light to the treatment of HNSC [50]. In conclusion, low-risk patients are more likely to bene t from immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we lumped together different therapeutic strategies into only a curative and palliative group. Although this makes sense from the patient's viewpoint, one should be aware that the obtained results would benefit from a more in-depth analysis-e.g., when comparing the effects of targeted therapy vs. immunotherapy vs. chemotherapy [32,46,47] or for surgery vs. radiation therapy [48]. In a recent review, it was shown that across most studies, QOL remained stable after treatment with stereotactic radiation therapy, but not after surgery [48].…”
Section: Discussionmentioning
confidence: 99%